Computational modelling of hydrogel therapies - Ahmed, Sadman Sakib (Department of Mechanical Engineering, 2025)
Myocardial infarctions (heart attacks) are a type of cardiovascular disease that affects a large population of people around the world. They lead to the death of heart tissue, which is eventually replaced by scar tissue in a non-reversible process. Scar tissue does not behave like normal heart tissue (myocardium), and this leads to a decrease in heart function and eventually, heart failure. Current areas of research regarding treatment of this disease look at using injectable biomaterials to provide mechanical support to existing scar tissue. This has been shown to improve heart function in various animal models. A popular biomaterial of choice is polyethylene glycol (PEG), chosen for its biocompatibility and other desirable qualities. PEG undergoes a gelation process, where it changes from a liquid to a gel via a chemical reaction. This is useful as it can be injected during its liquid state and can then solidify into a gel, over a certain period, at a location of interest. Previous in situ studies have noted that the gel that is injected in the myocardium is found in other parts of the body. This is undesirable as this may lead to adverse side effects if the gel solidifies elsewhere in the body. PEG is relatively expensive, and it is also of interest to optimize the procedure to use enough of it. The hypothesis for the gel ending up elsewhere in the body is that the greatest losses of the gel occur while it is a liquid. This research aims to answer the hypothesis by developing a computational framework that investigates the flow behavior of PEG present in rat myocardium as it undergoes gelation. A methodology is presented for characterizing the gelation of PEG from existing rheology data. A material model is developed for gelation by using a time-dependent viscosity model that is implemented numerically in Ansys Polyflow. A second methodology is presented for modelling the flow of PEG out of a domain of interest using existing FSI results. This methodology utilizes a traction boundary condition, which, when applied to a domain of interest, results in outflows out of all orifices. 2D computational studies are carried out to characterize the impact of applied traction on observed flow rate. The studies are done across the range of viscosities for which the liquid gel exists and explore the use of a time-dependent viscosity. This is done using an idealized, microfluidic geometry that is derived from literature. The findings from the 2D study are used to build a 3D model that uses realistic geometry of PEG contained in rat myocardium. 3D computational studies are conducted to explore the aforementioned hypothesis. The findings from the studies show the gel exists at its lowest viscosity for a relatively long period of time, during which it incurs significant losses out of the myocardium. The findings also show that for an initial increase in viscosity due to gelation, the rate at which the losses occur decreases significantly. However, subsequent increases in viscosity do not result in an equal decrease in the rate of loss; i.e., as viscosity increases during gelation, the rate at which losses occur decreases slowly. The work presented can be used to support the development of PEG for future studies and gives insight into optimizing the procedure for injecting PEG into myocardium. Furthermore, the framework can be used to investigate the flow behaviour of PEG when injected into different parts of the heart.